Familial dilated cardiomyopathy in a child: a case report - Ali Ismail; Dima Khreis; Amani Assaad; Marianne Nimah Majdalani (BMC, 2024)
Abstract Background Dilated cardiomyopathy (DCM) commonly leads to heart failure (HF) and represents the most common indication for cardiac transplantation in the pediatric population. Clinical manifestations of DCM are mainly the symptoms of heart failure; it is diagnosed by EKG, chest x-ray and echocardiography. For the idiopathic and familial diseases cases of DCM, there are no definite guidelines for treatment in children as they are treated for prognostic improvement. Case presentation We report the case of a 2-year-old girl diagnosed with dilated cardiomyopathy associated with homozygous mutation in the Myosin Light Chain 3 gene admitted for edema in lower extremities, muscle weakness, lethargy and vomiting, and she was found to be in cardiogenic shock. Chest x-ray showed cardiomegaly and EKG showed first degree atrioventricular block. Echocardiogram showed severe biventricular systolic and diastolic dysfunction. After 70 days of hospitalization, the patient went into cardiac arrest with cessation of electrical and mechanical activity of the heart, despite cardiopulmonary resuscitative efforts. Conclusion Although rare, pediatric DCM carries a high risk of morbidity and mortality and a lack of curative therapy.